2022
DOI: 10.1021/acsomega.1c06612
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensor for Quantitation of the Oral Health Care Agent Chlorogenic Acid Based on Bimetallic Nanowires with Functionalized Reduced Graphene Oxide Nanohybrids

Abstract: Chlorogenic acid (CGA), a phenolic acid from coffee, has been regarded as a powerful ingredient against oxidative stress and inflammation. Meanwhile, its healing feature to interfere with periodontal disease (PD) makes it a promising drug candidate. However, the existing methods for chlorogenic acid detection limit its practical application in purification and further pharmacological study in stomatology due to their lack of accuracy and productivity. Therefore, it is crucial to find a forceful approach to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies have shown that the main bioactive functions of CGA are antioxidant, anti‐inflammatory, antibacterial, antitumour, protecting liver and kidney, blood vessels and nervous system, regulating glucose metabolism and lipid metabolism (Wang, Pan, et al, 2022). CGA has a wide range of biological activities and the research on the biological activity of CGA in modern science has penetrated into many fields such as food, health care, medicine and daily chemical industry (Gupta et al, 2022; Li et al, 2020, 2023). Therefore, CGA is a bioactive substance with research and application prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the main bioactive functions of CGA are antioxidant, anti‐inflammatory, antibacterial, antitumour, protecting liver and kidney, blood vessels and nervous system, regulating glucose metabolism and lipid metabolism (Wang, Pan, et al, 2022). CGA has a wide range of biological activities and the research on the biological activity of CGA in modern science has penetrated into many fields such as food, health care, medicine and daily chemical industry (Gupta et al, 2022; Li et al, 2020, 2023). Therefore, CGA is a bioactive substance with research and application prospects.…”
Section: Introductionmentioning
confidence: 99%